The spatially resolved star formation law in nearby galaxies - Bigiel, Frank (2008)
This thesis presents a comprehensive analysis of the relationship between gas and star formation (SF) at sub-kpc resolution in a large sample of nearby galaxies. The analysis is based on recent very high quality radio, infrared and UV data. Key to this thesis are new, sensitive and high resolution atomic gas maps from "The HI Nearby Galaxy Survey" (THINGS). A combination of these multiwavelength data are used to study the gas-SF relation across the H2dominated centers of the spirals as well as their HIdominated outskirts and HIrich late type/dwarf galaxies. For the spiral galaxies, a Schmidt-type power law with index N = 1.0 ± 0.2 relates star formation rate and H2. This implies that H2 forms stars at a constant efficiency, i.e. star formation rate per unit gas, in spirals. Most galaxies show little or no correlation between the star formation rate and HI. The star formation efficiency is observed to decrease with increasing radius in the spirals, while the dwarf galaxies in our sample display star formation efficiencies similar to those found in the outer optical disks of the spirals...
Keywords: Hochschulschrift; Sternentstehung; Galaxie